A New Concept in the Begg Technique: The Separate Arch System - Ashikari Yoshinari (Sciendo, 1992)
The author reports on the Separate Arch System (SAS) he has devised by adapting basic Begg Technique concepts in the light of his clinical experiences. SAS, a multi-bracket arrangement using reverse light wire brackets, is a method of initiating orthodontic movement in the anterior and posterior segments separately, but completing them at the same time. The method's features include: a) use of thinner wire in segments and in multiple strands, as needed, maximising benefits of light force and differential anchorage; b) one-point rigidity in the wire-bracket relation; c) the method can be applied in both extraction and non-extraction cases; d) the patient's home care is simplified; e) the method is quick, simple, and systematic (thus making estimation of a therapy goal possible).